SISTEM MONITORING TERPADU PADA JASA LAUNDRY (STUDI KASUS MARKAS LONDRE) - Sigit Riyadi (STMIK YADIKA BANGIL, 2022)
Abstract: At the Headquarters of Londre Data management is still done manually or still using paper and customer laundry items is estimated based on instinct, which means that every time a customer comes in, their laundry will be finished based on instinct so that consumers will have difficulty knowing the laundry is in the process and sometimes on the appointed day it was over, it was still not finished. The employees also had difficulties during the process of managing and controlling, because the number of orders increased and the employees also had difficulty when differentiating the customer's laundry items that had entered the laundry stages.At the Londre Headquarters the monitoring process is still not available at that place. Therefore, this thesis will be made a